2017
DOI: 10.1016/j.jconrel.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable brain-penetrating DNA nanocomplexes and their use to treat malignant brain tumors

Abstract: The discovery of powerful genetic targets has spurred clinical development of gene therapy approaches to treat patients with malignant brain tumors. However, lack of success in the clinic has been attributed to the inability of conventional gene vectors to achieve gene transfer throughout highly disseminated primary brain tumors. Here, we demonstrate ex vivo that small nanocomplexes composed of DNA condensed by a blend of biodegradable polymer, poly(β-amino ester) (PBAE), with PBAE conjugated with 5 kDa polyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…We have previously demonstrated that NP up to 114 nm in diameters, if shielded with a dense layer of hydrophilic and neutrally charged polyethylene glycol (PEG; ≥ 9 PEG polymer chains per 100 nm 2 particle surface [6]), resist adhesive interactions with the brain ECM and rapidly diffuse within the healthy brain ICS [6, 18]. We have also shown that the ECM mesh spacings could be smaller depending on the type of tumor [19, 20]. More recently, we demonstrated that a marriage of CED and densely PEGylated NP enabled synergistically enhanced distribution of various therapeutic NP formulations following intracranial administration, while non-PEGylated or conventionally PEGylated NP were unable to do so [13-15, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that NP up to 114 nm in diameters, if shielded with a dense layer of hydrophilic and neutrally charged polyethylene glycol (PEG; ≥ 9 PEG polymer chains per 100 nm 2 particle surface [6]), resist adhesive interactions with the brain ECM and rapidly diffuse within the healthy brain ICS [6, 18]. We have also shown that the ECM mesh spacings could be smaller depending on the type of tumor [19, 20]. More recently, we demonstrated that a marriage of CED and densely PEGylated NP enabled synergistically enhanced distribution of various therapeutic NP formulations following intracranial administration, while non-PEGylated or conventionally PEGylated NP were unable to do so [13-15, 20].…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that the ECM mesh spacings could be smaller depending on the type of tumor [19, 20]. More recently, we demonstrated that a marriage of CED and densely PEGylated NP enabled synergistically enhanced distribution of various therapeutic NP formulations following intracranial administration, while non-PEGylated or conventionally PEGylated NP were unable to do so [13-15, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…The high density of PEG in these systems has been shown to greatly reduce, if not eliminate, toxicity caused by the cationic nature of PEI . Nanoparticles containing similar size and charge characteristics have been shown to penetrate brain tissue when infused intracranially, providing uniform reporter gene expression . ZsGreen‐BPN transfected tissue volume was assessed at 48 h postadministration.…”
mentioning
confidence: 99%
“…Two kinds of brain tumor are existed called benign and malignant 2 . Meningiomas and low grade gliomas are the other names of benign tumors, 3 whereas malignant tumors 4 are further named as glioblastoma multiforme and high grade gliomas. The most common occurred primary brain neoplasm is referred as malignant tumors.…”
Section: Introductionmentioning
confidence: 99%